Profil Komposisi BTP Campuran, Pelabelan, dan Penggunaannya pada Industri Rumah Tangga Pangan (IRTP) di DKI Jakarta - Dewi Monita Sari; Nuri Andarwulan; Dedi Fardiaz (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2019)
Mixed food additives had been registered at BPOM since 2012. However regulation concerning mixed food additives was issued in 2016 and applied in 2017. The compliance assessment regarding registered mixed food additives has not been conducted so far. This research was aimed to identify composition and the use of mixed food additives as declared on label, evaluate its compliance with regulation and its use by home food industries in Jakarta. The secondary data regarding the composition of mixed food additives were obtained from BPOM, while the primary data regarding the decralation of mixed food additives were obtained from the market in DKI Jakarta. The results showed that 78% (494/632) registered mixed food additives were flavoring and colouring mixed food additive. The composition of mixed food additives divided into 3 part, namely the primary food additive which has a technological function in the final food product, the secondary food additive which has a technological function on mixed food additives and other ingredients that determine mixed food additives form (liquid, solid, powder, and paste/semisolid). The level of label sample complied with the regulation were 57% (49/86). Regarding to survey result on 18 home food industry, 7 were founded to use 16 kinds of mixed food additives. The application of 4 among these 16 kinds of mixed food additives were exceeded based on maximum limit of the regulation that had been stated by BPOM.